(untitled) (Iter, 2022)
Rome was heir to Greek culture. From it the Romans learnt poetry, literature, philosophy and art. But Román creations, though inspired by the Greek genius, always expressed something original and unique. Such is also the case with sculpture. A contrast betw’een the Parthenon s Panathenaic procession and the bas-relief on the Ara Pacis brings out the profound continuity of ancient art, and at the same time the strong and distinctive personality of these peoples.